Optimasi Pemberian Air Irigasi Berdasarkan Penggeseran Jadwal Tanam Terhadap Luas Tanam Maksimum (Studi Kasus Daerah Irigasi Sekampung Batanghari Kabupaten Lampung Tengah) - Aniessa Rinny Asnaning; Muhammad Idris; Kelik Istanto (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2017)
Sekampung Batanghari Irrigation Area is one of the irrigation areas whose water supply comes from Argoguruh Dam. Lack of water discharge on weirs causes the cultivated area to be limited. The problem of water shortage needs to be given optimization solution of water distribution so that the area can be planted to maximum and can increase rice production.. Optimization analysis of channel in Sekampung Batanghari Irrigation Area was done using linear programming method by initial shifting cultivation in the first planting season when the availability of discharge in the channel was abundant with rice-rice-rice cropping pattern for three times of planting season. The optimization results that have been done by shifting the beginning of planting in January, February, May, August, and November show that the maximum plantable area that can be cultivated is 1,823.77 hectares per year that is on the initial shifting of the first planting season in January or May with intensity planting of 230%. While the minimum planting area that can be planted is 1,062.71 hectares per year on the initial shift of the first planting season in November.Kata kunci : optimization, irrigation, planting season